PERAN DINAS SOSIAL PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) - Putri Nur Azizah; Ananta Prathama (Journal Publicuho, 2024)
The Family Hope Program or Conditional Cash Transfers is one of the government's policies in providing a number of non-cash social assistance to poor or vulnerable people who have been registered in the integrated social welfare data. This research aims to analyze the role of the Nganjuk Regency Social Service in the Family Hope Program in Sumberkepuh Village, Tanjunganom District. This research uses a descriptive qualitative research method based on the community worker role theory according to Jim Ife and Tesoriero. The results of the research show that the role of facilitation, education, representation and techniques carried out by the Social Service for Women's Empowerment and Child Protection has been running effectively. So it can be concluded, that Social Service has played a good role in helping recipients to improve their quality of life so that they can achieve prosperity and get out of the poverty line.